Decisional reference point pathology: A cognitive mechanism for and a correlate of major depressive disorder in humans - Aadith Vittala; Lulu Wu; Dongni Yan; David Liebers; Elizabeth Tell; Xiaotong Song; Damon Dashti; Kenway Louie; Candace Raio; Dan V. Iosifescu; Paul W. Glimcher (Proceedings of the National Academy of Sciences, 2026)
The decisional reference point, the central mechanism underlying behavioral economics, conditions our evaluations of all reinforcers. Whether a given event is experienced as positive or negative depends on this reference point. A pathological elevation of the reference point would lead a person to experience once pleasurable activities as negative reinforcers. Thus, it has been hypothesized that a reference point pathology may play a critical role in the symptomology of major depressive disorder (MDD). Here, we test the hypothesis that the reference point is pathologically elevated and dynamically inflexible in patients suffering with MDD compared to healthy controls. We find that depression is associated with a significant elevation of the reference point, and the magnitude of this elevation correlates with disease severity. The ability of patients with MDD to dynamically adjust their reference point to the environment is also dysfunctional. Our findings link the previously demonstrated treatment of depression by deep brain stimulation to modulation of the reference point in the anterior cingulate cortex and identify pathology in the dynamics of reference point setting as a potential cognitive mechanism in the disorder. Finally, these results reveal that a three-minute video game-like task measuring the reference point strongly correlates with depression severity. After further testing for clinical validity, this rapid assay may serve as a potential tool for assessing and monitoring depression.